A comparative study of inter-abutment distance of dies made from full arch dual-arch impression trays with those made from full arch stock trays: An in vitro study - Reddy Jagan; Prashanti E; Kumar G; Suresh Sajjan M; Mathew Xavier (Wolters Kluwer Medknow Publications, 2009)
Objectives: The dual-arch impression technique is convenient in that it makes the required maxillary and mandibular impressions, as well as the inter-occlusal record in one procedure. The accuracy of inter-abutment distance in dies fabricated from dual-arch impression technique remains in question because there is little information available in the literature. Materials and Methods: This study was conducted to evaluate the accuracy of inter-abutment distance in dies obtained from full arch dual-arch trays with those obtained from full arch stock metal trays. Results and Conclusion: The metal dual-arch trays showed better accuracy followed by the plastic dual-arch and stock dentulous trays, respectively, though statistically insignificant. The pouring sequence did not have any effect on the inter-abutment distance statistically, though pouring the non-working side of the dual-arch impression first showed better accuracy.